Immunomodulatory Properties of a γ-Aminobutyric Acid-Enriched Strawberry Juice Produced by Levilactobacillus brevis CRL 2013 - Cataldo, Pablo G.; Villena, Julio; Elean, Mariano; Savoy de Giori, Graciela; Saavedra, Lucila; Hebert, Elvira M. (Frontiers in Microbiology, 2020)
Gamma-aminobutyric acid (GABA) plays a key role in mammals as the major inhibitory neurotransmitter of the central nervous system. Although GABA may not be able to cross the human blood-brain barrier, it was approved as a food ingredient because of its benefits to the host after oral administration including anti-hypertensive, anti-depressant and anti-inflammatory activities. Considering the current trend toward the development of new functional and natural products and that microbial fermentation is one of the most promising methods to produce this non-protein amino acid, the in situ production of GABA through fermentation of strawberry and blueberry juices by the efficient GABA producer strain, Levilactobacillus brevis (formerly known as Lactobacillus brevis) CRL 2013, was evaluated. A high GABA production (262 mM GABA) was obtained after fermenting strawberry juice supplemented with yeast extract for 168 h, being GABA yield significantly higher in strawberry juices than in the blueberry ones. Thus, GABA-enriched fermented strawberry juice (FSJ) was selected to carry out in vivo and in vitro studies. The in vitro functional analysis of the GABA-enriched FSJ demonstrated its ability to significantly decrease the expression of cox-2 gene in LPS stimulated RAW 264.7 macrophages. In addition, in vivo studies in mice demonstrated that both, L. brevis CRL 2013 and the GABA-enriched FSJ were capable of reducing the levels of peritoneal, intestinal and serum TNF-α, IL-6, and CXCL1, and increasing IL-10 and IFN-γ in mice exposed to an intraperitoneal challenge of LPS. Of note, the GABA-enriched FSJ was more efficient than the CRL 2013 strain to reduce the pro-inflammatory factors and enhance IL-10 production. These results indicated that the CRL 2013 strain exerts anti-inflammatory effects in the context of LPS stimulation and that this effect is potentiated by fermentation. Our results support the potential use of L. brevis CRL 2013 as an immunomodulatory starter culture and strawberry juice as a remarkable vegetable matrix for the manufacture of GABA-enriched fermented functional foods capable of differentially modulating the inflammatory response triggered by TLR4 activation.